Biography stigmatized with sufferring in Frida Kahlo`s narrations - Mendecka, Grażyna (Biografie nieoczywiste: Przełom, kryzys, transgresja w perspektywie interdyscyplinarnej, 2018)
The text presents biographical deliberations about Mexican artist-Frida Kahlo.Her fortunes and dufficult experiences concerning accident, her marriage, and unhappiness in relationships with men are reconstructed from paintings and another works.Frida Kahlo also kept a diary and lively correspondence in which she described her pain, worries and sorrows. But the most obvious narrative were her paintings, including autoportraits, in which she fully expressed herself. Frida masterfully built her narratives – using physical pain, nudity and sexuality to inform the world about her mental sufferings due to disability, betrayal of the closest, motherhood failure and loneliness.